Leaderboard as an Element of Gamification and Student Self-Efficacy for Performance Achievement - Aris Triwahyu Febriansah; Yerry Soepriyanto; Muhibuddin Fadhli (Jurnal Ilmiah Pendidikan Profesi Guru, 2024)
Less innovative learning activities have an impact on an unpleasant learning atmosphere. Project-based learning (PjBL) with a gamification approach presents innovative learning to increase motivation, engagement, and achievement of learner performance. As a gamification mechanism, the leaderboard provides feedback by reporting learner achievement and progress. This study aims to comprehensively analyze and provide evidence of the effect of the use of leaderboards and students' self-efficacy levels on their performance achievement in project-based learning. This study uses Quasi-experimental quantitative method with 2x3 factorial experimental design. The research sample consisted of 94 undergraduate students who took the Interactive Multimedia course. The data collection method used observation and questionnaires. The research instrument used a questionnaire sheet. Data were analyzed with inferential statistics using a two-way ANOVA test. The results showed a significant difference in the average performance score between the class that used the leaderboard and the class that did not use the leaderboard. The application of the leaderboard mechanism as a gamification method has a positive impact on students' learning achievement in project-based learning. The results also show that the level of self-efficacy has a significant impact on student achievement.